TRANSLATION PROBLEMS OF REALITIES IN GERMAN - LITERARY WORKS INTO UZBEK (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article deals with the translation problems of realities and their analysis in German. For this reason, translation problems of the realities have been investigated with many comparisons.